Experiencia de conservación ex-situ de Solanum fernandezianum (Solanaceae) Experience of Conservation ex-situ of Solanum fernandezianum (Solanaceae) - Jaime Solano (Universidad de Concepción, 2011)
Solanum fernandezianum is an endemic species in danger of extinction the Robinson Crusoe Island, Chile. The fruit was collected during March and April of 2002. The seeds were storaged for a year to 4°C. The percentage of germination in laboratory conditions was 14.3%. After 22 weeks plants initiated flowering and fruiting. The conservation strategy considered germination of seeds, production of plants in incubation chamber, transplantation to pots and pots arranged in a greenhouse.